Can China consume less coal?. - Sweet, W. (IEEE spectrum)
China's biggest single consumer of coal and emitter of carbon dioxide is electric power generation. Among industrial users of energy, it accounts for about a third of CO2 emissions, and among all users, about a quarter. In this paper, the authors argue that, although the electric power sector uses by far the most coal, better opportunities for reducing CO2 emissions exist elsewhere in China